Rancangan Pembelajaran Matematika Terintegrasi Islam melalui Problem Based Learning pada Materi Peluang Majemuk - Alghar, Muhammad Zia (Indonesian Journal of Teaching and Learning, 2024)
This study aims to examine the design of Islamic integrated mathematics learning through Problem Based Learning model on compound chance material. This research method uses a qualitative approach with the type of literature study. The learning model is carried out through problem-based learning (PBL) with an Islamic integration approach, namely mathematics to deliver al-Quran. The data used refer to various literatures such as the Qur'an, journal articles, books, and documents relevant to Islamic integrated mathematics. The results showed that Islamic integrated mathematics learning can be designed through PBL model on compound chance material. The stages in PBL model Islamic integrated learning are carried out through 5 stages, namely 1) orienting students to the problem, 2) organizing students, 3) guiding group investigations, 4) presenting work, and 5) evaluating the problem-solving process. This research contributes to providing a design for Islamic integrated mathematics learning with PBL models that can be applied and used for teachers and academics in the field of math education.